What governs the interannual variability of recurving North Atlantic tropical cyclones? - Sainsbury, Elliott M.; Schiemann, Reinhard K. H.; Hodges, Kevin I.; Baker, Alex J.; Shaffrey, Len C.; Bhatia, Kieran T. (American Meteorological Society, 2022)
Recurving tropical cyclones (TCs) can cause extensive damage along the US East Coast and later in their life cycle over Europe as post-tropical cyclones. While the existing literature attempts to understand the drivers of basin-wide and regional TC variability, less work has been undertaken looking at recurving TCs. The roles played by the interannual variabilities of TC frequency and the steering flow in governing recurving TC interannual variability are investigated in this study. Using a track-matching algorithm, we identify observed TC tracks from the HURricane DATabase version 2 (HURDAT2) in the ERA5 and MERRA2 reanalyses. This allows for detailed analysis of the post-tropical stages of the tracks in the observational TC record, enabling robust identification and separation of TCs that recurve. We show that over 75% of the interannual variance in annual recurving TC frequency can be explained by just two predictors – the frequency of TCs forming in the subtropical Atlantic, and hurricanes (TCs with wind speeds > 33ms-1) forming in the Main Development Region. An index describing the seasonal mean meridional steering flow shows a weak, non-significant relationship with recurving TC frequency, supported by composite analysis. These results show that the interannual variability in recurving TC frequency is primarily driven by the seasonal TC activity of the MDR and the subtropical Atlantic, with seasonal anomalies in the steering flow playing a much smaller, secondary role. These results help to quantify the extent to which skillful seasonal forecasts of Atlantic hurricane activity benefit regions vulnerable to recurving TCs.